Confinamento das moléculas H2 e O2 como modelo para o estudo da ligação ligante-sítio ativo em macromoléculas biológicas - Silva, Fabrício Ramos [UNESP] (2014)
This works presents the energy eigenvalues for the bonds of hydrogen and oxygen molecules, both confined in elliptical cavities. Those systems are also studied without confinement. The results are obtained through the variational method and supersymmetric quantum mechanics. The supersymmetry permits to determine the atomic orbitals. The Hückel approximation is used to justify the similar stability between and bonds in the oxygen molecule. The obtained results to the molecular chemical bonds (hydrogen and oxygen molecules) shown a stability region of energy interns of the confinement volum. Finally, possible applications for systems involving protein active sites are discussed